Faktor yang Mempengaruhi Kepuasan Pengguna Coretax dan Dampaknya terhadap Kepatuhan Wajib Pajak Bendahara Pemerintah - Ines Saraswati Machfiroh; Astia Putriana; Mahmudah; Memey Ifalia Kristin; Muhammad Wildan (Owner : Riset dan Jurnal Akuntansi, 2026)
This research aims to test and analyze the influence of system quality, information quality, and service quality on user satisfaction of CoreTax. Additionally, it examines and analyzes the effect of user satisfaction on taxpayer compliance. This study is a quantitative research with a causal design. The population of this research consists of government treasurer taxpayers. The sample was determined using purposive sampling with the criteria of government taxpayers within the Local Government Work Unit (SKPD) of Tanah Laut Regency who manage taxation using CoreTax namely 96 respondents. This type of data uses primary data through distributing questionnaires to respondents via Google forms. The data analysis method used is Structural Equation Modeling with SmartPLS. The results indicate that system quality and service quality have an impact on user satisfaction of CoreTax. On the other hand, information quality does not affect user satisfaction of CoreTax. Furthermore, user satisfaction does not influence taxpayer compliance. This research provides insights into the need for the development of CoreTax systems and services to support user satisfaction and the need to develop systems and services that support the psychological needs of taxpayers so that the system not only provides satisfaction, but also builds internal motivation to comply.